KEPATUHAN KONSUMSI TABLET BESI FOLAT PADA IBU HAMIL DAN FAKTOR YANG MEMPENGARUHI - Rahmawati, Febriana; Subagio, Hertanto Wahyu (Journal of Nutrition College, 2012)
Backgrounds : Anemia in pregnant women can effect maternal death, increased fetal morbidity and mortality. Iron supplementation programs should have a high success rate because the iron folate tablets are easily available and free of charge. But in reality. the compliance rate of iron folate tablets is still lowPurpose: analyze compliance rate of iron folate tablets in pregnant women at Puskesmas Halmahera and the factors influenced.Method: An analytic observational research with cross-sectional design. The subjects in this study is 56 pregnant women who went on Puskesmas Halmahera. Subject was taken by consecutive sampling technique with the criteria pregnant women trimester 2 and 3. Compliance data, knowledge, education, family support and health care obtained through interviews with a questionnaire. Normality of data was tested using Kolmogorov-Smirnov. Bivariate analyzes performed using Rank Spearman testResult: there is a association between knowledge scores with compliance (r = 0.370, p = 0.005), there is no significant association between education level and compliance (r = 0.032, p = 0.817 there is no significant association between family support and compliance (r = 0.216, p = 0.115) and there is no significant association between health service and compliance (r = 0.217, p = 0.108)Conclusion: more than a half of respondents (58,9%) did not comply consume iron folate tablets. Based on the data can be seen that the knowledge is the most influental factor.